Collateral, credit history, and the financial decelerator - Elul, Ronel (Journal of Financial Intermediation, 2008)
We develop a simple model of the housing market in which financial imperfections can serve to stabilize aggregate fluctuations, and not necessarily aggravate them as in much of the previous literature; we term this a financial decelerator. Stabilization can occur in our model because lenders are imperfectly informed as to borrowers' propensity to default. As a result, it is too costly for lenders to impose borrowing constraints that guarantee repayment in every possible eventuality. This allows some borrowers to default when house prices are low, thereby leaving them with more wealth. This then serves as an endogenous stabilizing force.